Research on economical sawing equipment for auto roll-forming frame part adapted to fast switching of multiple varieties. Issue 6 (January 2021) - Peng, Li-Ming; Qian, Hua-Min
Abstract: Precise angle sawing is an important process to ensure the auto roll-forming frame parts be assembled and welded accurately. Large enterprises can adopt special sawing machine and fixture to meet the requirements. However, this method is not suitable for small enterprises due to its large investment and insufficient flexibility of the manufacturing system. Considering the multi-varieties and small batches production characteristics, economical sawing equipment based on the general cutting machine platform equipped with quick change fixture is introduced. By changing the fixture position on the platform, and replacing a few necessary elements, this equipment can accomplish different angle precise sawing for various auto roll-forming frame parts. Finally the economical technology renovation purpose is realized.